Medical personnels’ well-being and policy adaptations in hospitals during COVID-19 pandemic - Kristian, Kevin; Santi, Bryany Titi; Astiarani, Yunisa; Kurniawan, Felicia; Salama, Ngabila (Universitas Gadjah Mada, 2022)
Purpose: To explore many forms of adaptations and alterations that occur in the COVID-19 referral hospitals in Jakarta during the COVID-19 pandemic as a preparation to deal with another pandemic in the future. Method: A qualitative study through focus group discussions (FGD) of seven hospitals in Jakarta, including five public and two private hospitals, with the participation of each structural and medical personnel separately. The discussion identifies four main topics that cover the aim of the study: (a) Medical personnel workload; (b) Occupational health and comfort; (c) Relationships; (d) Hospital policy during the COVID-19 pandemic. Results: This study was participated by 40 informants from the medical personnel group and 37 responders from the structural group from various positions in the hospital. Researchers estimated several factors to contribute to medical personnel’s well-being in providing health services during the pandemic of COVID-19. Rising workloads, an increased number of patients and types of procedures, and the unavailability and discomforts from suitable PPE with a lack of IPC socialization influence a decline in their well-being and increase the risk of counterproductive work behavior. Moreover, conflicts among personnel and poor communication also deteriorate well-being. Nevertheless, several hospital policy adaptations, namely incentives provision, regular mental-health check-ups, no salary reduction for COVID-19-positive workers, and supportive attitudes towards each other in the workplace, may enhance their well-being. Conclusion: Increased workloads, problems in PPE availability, and conflict among personnel are the main contributing factors that need to be addressed to increase the medical personnel's well-being during the pandemic, while several hospital policy adaptations support their well-being.